2019
DOI: 10.1097/corr.0000000000001081
|View full text |Cite
|
Sign up to set email alerts
|

External Validation of PATHFx Version 3.0 in Patients Treated Surgically and Nonsurgically for Symptomatic Skeletal Metastases

Abstract: Background PATHFx is a clinical decision-support tool based on machine learning capable of estimating the likelihood of survival after surgery for patients with skeletal metastases. The applicability of any machine-learning tool depends not only on successful external validation in unique patient populations but also on remaining relevant as more effective systemic treatments are introduced. With advancements in the treatment of metastatic disease, it is our responsibility to patients to ensure cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
82
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(84 citation statements)
references
References 13 publications
2
82
0
Order By: Relevance
“…This is contrary to the traumatic hip fracture scenario, where total hip arthroplasty is associated with better functional outcome [18] . Prognostication tools allow for choice of patients with MBD who are expected to have longer survival and thus benefit from total hip arthroplasty [19] , [20] .…”
Section: Discussionmentioning
confidence: 99%
“…This is contrary to the traumatic hip fracture scenario, where total hip arthroplasty is associated with better functional outcome [18] . Prognostication tools allow for choice of patients with MBD who are expected to have longer survival and thus benefit from total hip arthroplasty [19] , [20] .…”
Section: Discussionmentioning
confidence: 99%
“…PATHFx) using techniques such as machine learning requires accurate inputs of multiple factors predicting patient outcome. [9,10] By furthering our understanding of surgical technical factors that are related to overall patient survival, we can more accurately counsel patients on treatment goals, and modify surgical techniques accordingly. Interestingly, while surgical technique was not statistically associated with metastatic progression in the lung in this study, we did demonstrate that those who underwent IMN xation experience a poorer prognosis than those undergoing reconstruction with either arthroplasty or ORIF techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The model includes both objective quantifiable variables (age, sex, primary type, Eastern Cooperative Oncology Group performance status score, presence of visceral metastases, presence of multiple skeletal metastases, pathological fracture, hemoglobin, and lymphocyte count), and subjective variables (surgeon’s estimate of survival), although it has been reported that prognosis can be accurately predicted without this subjective variable [ 9 ]. PathFx has been externally validated in many different patient populations [ 9 , 10 , 11 , 12 ] and has been recently updated to PathFx version 3.0 ( accessed on 10 July 2021) [ 13 ]. Meares et al [ 14 ] compared several models, including the revised Katagiri model [ 15 ], SSG score [ 16 ], Janssen nomogram [ 17 ], and SPRING 13 nomogram [ 18 ], and reported that OPTModel demonstrated the highest accuracy at predicting 12-month (area under the curve [AUC] = 0.79) and 24-month survival (AUC = 0.77) after surgical management, while PathFx was the most accurate at predicting 3-month (AUC = 0.70) and 6-month survival (AUC = 0.70).…”
Section: Prognosismentioning
confidence: 99%
“…The final model was incorporated into a freely accessible web application available at accessed on 10 July 2021 [ 19 ]. Table 3 summarizes the prognosis prediction model created by machine learning [ 9 , 10 , 11 , 12 , 13 , 14 , 19 , 20 , 21 , 22 , 23 ]. Errani et al analyzed 159 patients with bone metastases in the extremities who underwent surgery [ 24 ] and reported that pathological CRP (≥1.0 mg/dL) and primary tumor diagnosis were significant negative prognostic factors at 12-month survival.…”
Section: Prognosismentioning
confidence: 99%